Principles and Practice of SPORT MANAGEMENT - Masteralexis, Lisa Pike; Hums, Mary A. (Jones & Bartlett Learning, 2024)
"Principles and Practice of Sport Management provides students with the foundation they need to prepare for a variety of sport management careers. Intended for use in introductory sport management courses at the undergraduate level, the focus of this text is to provide an overview of the sport industry and cover basic fundamental knowledge and skill sets of the sport manager, as well as to provide information on sport industry segments for potential employment and career opportunities"--